2016
DOI: 10.3390/f7110286
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Acceptability of Implementing Marker-Assisted Selection in the Forests of British Columbia

Abstract: Abstract:The forest sector in British Columbia (BC) has faced a number of challenges over the past decade. In response to some of those challenges, the government has invested in forest genomic tools. Marker-assisted selection (MAS) is a biotechnological tool that flags desired traits on the genome. This tool may assist tree breeders with the early selection of preferred genotypes, reducing the breeding cycle and more accurately and efficiently selecting for improved qualities. However, there is a poor underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…Savadori et al (2004), for example, found that experts (i.e., professors and Ph.D. students in biology) viewed food and medical technologies such as GE as less risky and more useful than did the public. Similar patterns have been found in the context of forestry (Hajjar et al, 2014;Jepson & Arakelyan, 2017b;Nilausen et al, 2016). Nilausen et al (2016), for example, found that representatives of government agencies and the forest industry were more supportive of using technologies related to breeding and genetics in forestry than were citizen organizations (i.e., NGOs) and indigenous pop-ulations.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Savadori et al (2004), for example, found that experts (i.e., professors and Ph.D. students in biology) viewed food and medical technologies such as GE as less risky and more useful than did the public. Similar patterns have been found in the context of forestry (Hajjar et al, 2014;Jepson & Arakelyan, 2017b;Nilausen et al, 2016). Nilausen et al (2016), for example, found that representatives of government agencies and the forest industry were more supportive of using technologies related to breeding and genetics in forestry than were citizen organizations (i.e., NGOs) and indigenous pop-ulations.…”
Section: Discussionsupporting
confidence: 65%
“…Assessing group differences in normative acceptance of natural resource issues has been a prominent line of research, especially between the public and other interest groups (e.g., scientists, agencies; Vaske & Whittaker, 2004). Studies have shown, for example, that nongovernmental organizations (NGOs), indigenous groups, and the general public can be less accepting of some issues, such as breeding or GE in forestry, compared to other groups such as scientists and industry representatives (Hajjar, McGuigan, Moshofsky, & Kozak, 2014; Jepson & Arakelyan, 2017b; Nilausen, Gélinas, & Bull, 2016).…”
Section: Conceptual Foundationmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the enormous investment in resources that have been expended to identify markers, very few operational breeding programs for either crops or trees use MAS (Isik 2014;Muranty et al 2014;Neale and Kremer 2011;Xu and Crouch 2008). Several factors have contributed to this, but often markers associated with QTLs are identified in studies using a relatively small number of progeny, and consequently they may not be useful when tested in other families because the markers are not located sufficiently close to the genes responsible for the trait of interest (Nilausen et al 2016). In addition, traits like resistance are often complex, so it can be difficult to detect all the different loci involved.…”
Section: Genetic Tools To Accelerate Restoration and Facilitate Managementmentioning
confidence: 99%
“…Cost effectiveness of MAS: MAS has been proven to successful technique for selection of desirable plants in segregation population without linkage drag, pyramiding disease resistance gene and shortens period of releasing new cultivars. But the usage of MAS is restricted to traits with monogenic inheritance, laboratory with highly technical equipment and well trained scientific human resource as well as operation resource (Nilausen et al, 2016;Yang et al, 2016). The reliability and reproducibility of QTL based marker is unpredictable because of these types of markers were developed only in limited period of time/locations.…”
Section: Single-nucleotide Polymorphism (Snp)mentioning
confidence: 99%